Custos de transação e estrutura de governança: uma análise do processo de financeirização nas organizações de varejo - Lanzini, Luiz Eduardo (2014)
The present study focuses on describing the governance structures of retail companies in Brazil based on the works of Oliver Williamson and his contribution to Transaction Cost Economics. The model allows an estimation of behavioral assumptions and also the determinants theory raised by the recent phenomenon of financialization observed in the economic environment for these companies. Through longitudinal data and institutional documents findings that form organizational interpretations of choices as regards its structure was analyzed. The study from the perspective of this economic theory allowed the subjects to be examined from different perspectives across disciplines related to organizational studies in strategy area and the financial theory of capital structure for the choice of the study variables. The description of the institutional environment pointed to the conditions of opportunism for retail organizations in relation to credit. The econometric model generated indicated that there is statistical significance for the variables - frequency, specificity and expertise represented by the indicators - asset turnover, immobilization of equity and working capital respectively in the configuration of the governance structure, represented by the indicator of financial leverage. The documentary analysis showed evidence of structural configuration of some cases about the financial service credit.